Pengaruh Massage Dan Hot Bath Terhadap Penurunan Kelelahan Pada Pemain Futsal - UlHaq, Syuja', Isnaini Herawati, S.Fis, S.Pd, M.Sc, Yulisna Mutia Sari , SST.FT, M.Sc (2016)
Background: In the sport of futsal players often experience fatigue at the time of the match, Fatigue is a decreased ability to perform physical activity, general symptoms of fatigue closer is the sense of physical fatigue or physical fatigue and mental fatigue or mental fatigue. Other interventions that can be provided to reduce fatigue among others, is the provision of a hot bath and massagW. Objective: This study aims to determine the effect of massage and hot bath against fatigue in futsal players. Methods: This research is a quantitative type of quasi-experimental, with the approach of pre and post test design. Samples were 30 taken through purposive sampling method, measurement in research using the Visual Analogue Scale for Fatigue (VAS-F) to measure the value of the degree of pain. Results: From the results of the comparative test Wilcoxon test in the massage group matches p <0.05, indicating no effect of massage to fatigue, the group hot bath to get the p <0.05, indicating no effect of a hot bath against fatigue, Interpretation of results comparative test of Mann-Whitney test the effect of different massage and hot bath against fatigue in futsal players get a significant p value of 0.000, which means there are different effect of massage and hot bath against fatigue in futsal players. Conclusion: There is the influence of massage and hot bath against fatigue in futsal players.